The red maze / 5 Worlds - Siegel, Mark, 1967-; Siegel, Alexis; Bouma, Xanthe; Sun, Boya; Rockefeller, Matt (2019)
"Oona, Jax Amboy, and An Tzu must light the beacon on Moon Yatta and stop the evil force that threatens to rule the 5 worlds"--
Ages 8-12
Keywords: Graphic novels; Heroes -- Fiction; Adventure and adventurers -- Fiction; Science fiction; JUVENILE FICTION / Comics & Graphic Novels / General; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic; Graphic novels